Rural Marketing: Text and Cases - Agarwal, Sandeep (Indian Journal of Marketing, 2012)
The book provides specific reasons for the growing importance of rural markets and defines some key relevant concepts. It focuses on all the important components of rural marketing such as opportunities in rural marketing, understanding the rural economy, consumer behavior, selecting and attracting markets, understanding on strategic approach on marketing-mix 4P's, marketing of consumer products, agri-products, rural industry products and social marketing in rural society. The book holds various strategic and managerial implications for marketers, and researchers engaged/interested in India's vast rural market. The book is divided into six parts, which encompasses eighteen chapters to elaborate all such details. Book: Rural Marketing: Text and Cases Author(s): C.S.G. Krishnamacharyulu & Lalitha Ramakrishnan Publisher: Pearson Education Edition: Second ISBN: 978-81-317-3263-2 Price: INR 399.00 Pages: 608 pages Binding: Paperback